2014
DOI: 10.1590/0103-8478cr20131574
|View full text |Cite
|
Sign up to set email alerts
|

Produção e qualidade pós-colheita de cultivares de pereira nas condições subtropicais da região leste paulista

Abstract: Objetivou-se avaliar o desempenho produtivo e a qualidade pós-colheita de cultivares de pereira nas condições subtropicais da região leste paulista. Para tanto, um ensaio de competição de cultivares foi implantado no município de Jundiaí-SP, com cinco cultivares ('Centenária', 'Triunfo', 'Primorosa', 'Seleta' e 'Tenra'). O experimento foi implantado em 2007, no espaçamento de 3,0mx4,0m, com mudas enxertadas no porta-enxerto Pyrus calleryana. As avaliações foram realizadas em três ciclos vegetativos (2009/10, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…European pears; conversely, have the capacity to complete the ripening process post harvest. Number of days that lapse between the date of full bloom and harvest point was used as the indicator of the maturation index of the hybrid pear (BETTIOL NETO et al, 2014). The authors reported a mean value of 138 days and fruit length and diameter were estimated, as well as the post-harvest variables including color, firmness, titratable acidity, and soluble solids, besides others.…”
Section: Introductionmentioning
confidence: 99%
“…European pears; conversely, have the capacity to complete the ripening process post harvest. Number of days that lapse between the date of full bloom and harvest point was used as the indicator of the maturation index of the hybrid pear (BETTIOL NETO et al, 2014). The authors reported a mean value of 138 days and fruit length and diameter were estimated, as well as the post-harvest variables including color, firmness, titratable acidity, and soluble solids, besides others.…”
Section: Introductionmentioning
confidence: 99%
“…However, Pyrus rootstocks provide very vigorous crowns, which makes it difficult to conduct plants in high-density orchards (Bettiol Neto et al, 2014). Nonetheless, rootstocks of the Pyrus genus could be an option to provide vigor for quince cultivars, considering that some of them have a slow initial development in the early post-planting years, when propagated by cuttings or grafting (Bettiol Neto et al, 2011), and others have low-rooting capacity (Celant et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the pear being a fruit from temperate climates, there are some cultivars adapted to a subtropical climate (BETTIOL NETO et al, 2014;TECCHIO et al, 2011); the cultivation of this fruit in regions with mild winters is possible due to hybrid cultivars (Pyrus communis x P. pyrifolia) known as hardy pears. These cultivars were obtained by hybridisation between European pears (high winter cold requirement and excellent fruit quality) and oriental pears (low winter cold requirement and inferior fruit quality), developed in past decades by the Campinas Agronomic Institute (BARBOSA et al, 2007, BETTIOL NETO et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…These cultivars were obtained by hybridisation between European pears (high winter cold requirement and excellent fruit quality) and oriental pears (low winter cold requirement and inferior fruit quality), developed in past decades by the Campinas Agronomic Institute (BARBOSA et al, 2007, BETTIOL NETO et al, 2014. SEIFERT et al, 2009).…”
Section: Introductionmentioning
confidence: 99%